2018
DOI: 10.1002/1878-0261.12183
|View full text |Cite
|
Sign up to set email alerts
|

Biomarker potential of ST6GALNAC3 and ZNF660 promoter hypermethylation in prostate cancer tissue and liquid biopsies

Abstract: Current diagnostic and prognostic tools for prostate cancer (PC) are suboptimal, leading to overdiagnosis and overtreatment. Aberrant promoter hypermethylation of specific genes has been suggested as novel candidate biomarkers for PC that may improve diagnosis and prognosis. We here analyzed ST6GALNAC3 and ZNF660 promoter methylation in prostate tissues, and ST6GALNAC3,ZNF660,CCDC181, and HAPLN3 promoter methylation in liquid biopsies. First, using four independent patient sample sets, including a total of 110… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 65 publications
1
41
0
Order By: Relevance
“…Previous studies reveals that DNA methylation plays an important role in the development of prostate cancer and associates with adverse clinical outcomes. The methylation state of promoters of specific genes were also involved in the development of prostate cancer [11, 18, 19]. Larsen et al [20] reported that DNA-methylation analysis of urine cells captured by microfiltration provides a novel tool for noninvasive detection of high-grade prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reveals that DNA methylation plays an important role in the development of prostate cancer and associates with adverse clinical outcomes. The methylation state of promoters of specific genes were also involved in the development of prostate cancer [11, 18, 19]. Larsen et al [20] reported that DNA-methylation analysis of urine cells captured by microfiltration provides a novel tool for noninvasive detection of high-grade prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, ZNF660 me , CCDC181 me , ST6GALNAC3 me and HAPLN3 me in serum displayed 22%, 26%, 31% and 44% sensitivity, respectively, and 100% specificity for PCa. Remarkably, the best gene panel (ST6GALNAC3 me , CCDC181 me and HAPLN3 me ) increased sensitivity to 67%, keeping 100% specificity [178].…”
Section: Screening and Diagnosismentioning
confidence: 96%
“…SERPINB5 and AIM1 , the only markers found to have significant associations with progression [ 95 ] and overall survival [ 85 ] have only been investigated in two small independent studies each thus far, and require further validation in larger cohorts. And finally, new candidate genes from different biological pathways have been explored recently (e.g., PD1− , PD-L1 , CDO1 , TFF3 , ZNF660 ) [ 108 , 109 , 110 , 111 , 112 ] and also require further validation.…”
Section: Current State Of Prognostic Methylated Biomarkersmentioning
confidence: 99%